Lithium composite negative electrode with self-contained tabs and lithium battery including the lithium composite negative electrode
By designing a structure with its own electrode in the lithium composite negative electrode of a lithium battery, and using a conductive adhesive layer to bond the current collector layer and the electrode ear together, the problem that the lithium battery composite negative electrode cannot be directly produced in the prior art is solved, and the uniform thickness of the composite negative electrode and the simplification of industrial production are achieved.
Patent Information
- Application Number
- CN202420287568.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2034-02-07
AI Technical Summary
In existing lithium batteries, after carbonaceous film or other conductive film materials are combined with metal lithium negative electrodes, the electrode ears cannot be directly made, and the electrode ears of the metal foil need to be drawn out, and the thickness uniformity of the electrode sheet is poor, making it difficult to achieve simple and fast industrial production.
A lithium composite negative electrode with its own electrode ear is designed. By forming a conductive adhesive layer between the current collector layer and the electrode ear, the current collector layer and the electrode ear are bonded together by using the adhesiveness of the conductive glue to form a current collecting whole to ensure the stability of the electrode ear and the uniform thickness of the negative electrode layer.
The solution of the current collector film material in the industrial production of lithium batteries is realized, ensuring the surface flatness and overall thickness uniformity of the composite negative electrode, simplifying the production process, and suitable for large-scale mass production.
Smart Images

Figure CN222705535U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of electrochemical energy storage, in particular to a lithium composite negative electrode for a lithium battery. Background Art
[0002] As society's requirements for the energy density of lithium-ion batteries are getting higher and higher, the current research direction is turning to negative electrode materials with higher specific capacity. Metallic lithium is considered to be the best negative electrode material due to its capacity of 3860mAh / g and low potential of -3.04V. In addition, to increase the energy density of the battery, it is necessary to reduce the proportion of inactive substances. For the current collector, although the weight of the current collector copper foil can be reduced by continuously thinning the thickness of the copper current collector, the density of metallic copper is 8.96g / cm 3 , the thinnest 4um thick copper foil (4um thick copper foil is easy to break) is still equivalent to 67um thick lithium metal. Currently, carbon film materials with certain conductivity or other flexible conductive film materials are being developed to replace the current collector copper foil. The density of carbon film materials is 1g / cm 3 It can be a good substitute for the traditional current collector; but the problem is that after the relevant film materials are composited with the metal lithium negative electrode, the carbon film materials or other conductive film materials cannot be used directly as the pole ears, and the pole ears of the metal foil materials need to be led out for welding and use; and how to lead out the pole ears simply and quickly, and the led-out pole ears and carbon film materials form a current collector as a whole, and the thickness uniformity of the pole pieces is good (the thickness tolerance is less than 5um), which requires special design. Utility Model Content
[0003] In view of the above problems, the utility model provides a lithium composite negative electrode with a self-contained tab.
[0004] The utility model adopts the following technical solutions:
[0005] A lithium composite negative electrode with a built-in tab comprises: two negative electrode layers, an upper and a lower negative electrode layer, and a current collector layer sandwiched between the two negative electrode layers, wherein the width of the current collector layer is greater than that of the negative electrode layer, one end of the current collector layer is aligned with the negative electrode layer in the width direction, and the other end has a portion exposing the negative electrode layer, and a tab, wherein the portion of the current collector layer exposing the negative electrode layer and the tab are combined together through a tab bonding portion.
[0006] In certain embodiments, the tab bonding portion is an adhesive layer located between the portion of the exposed negative electrode layer and the tab.
[0007] In some embodiments, the adhesive layer is formed of a conductive adhesive, which can be pre-formed on the portion of the current collector layer that exposes the negative electrode layer, or pre-formed on the tab. With the help of the viscosity of the conductive adhesive layer, a partial area of the current collector layer and a partial area of the tab can be well bonded together.
[0008] In certain embodiments, by means of pressure lamination, the tab bonding parts can fit more closely and the current collection effect is better.
[0009] In some embodiments, the tensile strength at the tab bonding portion is greater than or close to the tensile strength of the current collector. For example, if the tensile strength of the current collector is 80 MPa and the tensile strength of the tab is 200 MPa, the tensile strength at the tab bonding portion is approximately equal to 80 MPa or close to 80 MPa.
[0010] In certain embodiments, the width of the adhesive layer is 2-10 mm.
[0011] In certain embodiments, the thickness of the tab is 4-50 um, preferably 6-20 um.
[0012] In certain embodiments, the negative electrode layer is a metallic lithium layer or a lithium alloy layer.
[0013] In some embodiments, the current collector film material is a carbon film material or other flexible conductive film material.
[0014] In some embodiments, the tab is made of metal foil.
[0015] In some embodiments, the thickness of the negative electrode layer is 1-100 um and the width is 50-1400 mm.
[0016] In certain embodiments, the lithium composite negative electrode is a continuous web having a length of 1-2000 m.
[0017] The utility model also provides a lithium battery, which comprises the above-mentioned lithium composite negative electrode with its own pole ear.
[0018] The utility model has at least one of the following advantages:
[0019] (1) The lithium composite negative electrode with its own tabs of the utility model solves the problem of tabs being introduced in the industrial production of current collector film materials (except metal current collectors).
[0020] (2) The lithium composite negative electrode with built-in tabs of the utility model has a smooth surface and good overall thickness uniformity because the width of the current collector film is greater than the width of the negative electrode layer and the tab bonding portion and the location of the tab are not in the negative electrode area.
[0021] (3) The production process of lithium composite negative electrodes with built-in tabs is simple and easy to operate, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the composite negative electrode structure of the utility model.
[0023] 1- negative electrode layer, 2- current collector layer, 3- tab, 4- tab bonding part. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the utility model more clear, the specific implementation of the utility model is described in detail below with reference to the accompanying drawings. It should be understood that the technical features involved in each implementation described below can be combined with each other as long as they do not conflict with each other.
[0025] One aspect of the utility model provides a lithium composite negative electrode with a self-contained tab. Figure 1 As shown, the lithium composite negative electrode of the utility model includes two negative electrode layers 1, a current collector layer 2 sandwiched between the two negative electrode layers and a pole ear 3 located outside the negative electrode layer. The pole ear 3 and the part of the current collector layer 2 exposed from the negative electrode layer are bonded by a pole ear bonding part 4.
[0026] In the lithium composite negative electrode of the utility model, the negative electrode layer (active material) is made of metallic lithium or lithium alloy, the film material of the current collector layer is made of carbon film material or other flexible conductive film material; the tab is made of metal foil material.
[0027] According to one embodiment, the active material can be distributed over most of the current collector layer by coating, pressure lamination, and vapor deposition processes, with one end of the active material aligned with the current collector layer in the width direction and the other end being smaller than the width of the negative electrode current collector.
[0028] According to one embodiment, the thickness of the active material metal lithium or lithium alloy (thickness of the negative electrode layer) can be 1-100 um, preferably 1-20 um; the width is 50-1400 mm, preferably 200-700 mm.
[0029] According to one embodiment, the lithium alloy is formed by a combination of metallic lithium and any one or at least two elements of Ag, Au, Sn, Si, Zn, Al, Mg, In, Ga, B, Mn, Sb, Bi, Cr, C, V, Cu, Fe or Ti.
[0030] According to one embodiment, the thickness of the current collector layer is 5-50 um, preferably 5-20 um.
[0031] According to one embodiment, the tab is made of metal foil, including copper foil, nickel foil, and stainless steel foil; the thickness of the metal foil is 4-50um, preferably 6-20um; the width of the tab can be 15-40mm.
[0032] According to one embodiment, the width of the tab bonding portion is 2-10 mm, which can be formed by first bonding the conductive adhesive to the edge area of the tab or first bonding to the edge area on the width of the current collector.
[0033] The lithium composite electrode can be prepared by the following method, which comprises:
[0034] The current collector layer and the tab foil are unwound first, and at least one of the edge regions of the current collector layer and the tab foil has a conductive adhesive. After the gluing positions of one side edge region of the current collector and one side edge region of the tab are adjusted, one side edge of the current collector and one side edge of the tab are formed into a complete whole by rolling pressure and the adhesion between the materials. Then, the upper and lower rolls of the metal lithium product are unwound, and pressure composite is performed to obtain a lithium composite negative electrode with a tab.
[0035] Another aspect of the utility model provides the use of the composite negative electrode with a self-contained tab in a lithium battery.
[0036] According to one embodiment, the lithium battery comprises the above-mentioned lithium composite negative electrode, and the positive electrode material is selected from ternary nickel-cobalt-manganese material, ternary nickel-cobalt-aluminum material, lithium-rich manganese-based positive electrode material, lithium cobalt oxide, lithium iron phosphate, and sulfur-based positive electrode material.
[0037] According to one embodiment, the electrolyte of the lithium battery can be selected from a liquid electrolyte or a solid electrolyte; the liquid electrolyte can be selected from an ester or an ether; the solid electrolyte can be selected from a halide solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, a polymer electrolyte or an organic-inorganic mixed electrolyte, such as a polyethylene oxide (mixed oxide, halide or sulfide powder) electrolyte.
[0038] For liquid batteries, the diaphragm is made of PP, PE or PP and PE laminated diaphragm, and the diaphragm can have a ceramic coating or a polyvinylidene fluoride coating.
[0039] The battery style can be square, soft pack or cylindrical.
[0040] The present invention is illustrated below by way of examples. The various product structural parameters, various reaction participants and process conditions used in the following examples are all relatively typical examples. However, after a large number of experiments and verifications by the inventor of this case, other different structural parameters, other types of reaction participants and other process conditions listed above are also applicable and can also achieve the technical effects claimed in this utility model.
[0041] Example 1
[0042] The tab uses a 10um thick copper foil with a width of 30mm and a length of 1000 meters. A 5mm wide conductive adhesive layer is applied to the edge area of one side of the copper foil, and no conductive adhesive is applied to other areas of the copper foil.
[0043] At the same time, a 150mm wide carbon nanotube film (8um thick) and a 30mm wide copper foil coated with conductive adhesive are unrolled. After the 5mm wide conductive adhesive layer area of the copper foil and the 5mm wide area at the edge of the carbon nanotube film are completely matched, the carbon nanotube film and the copper foil are rolled by a rolling equipment to become an integrated film material.
[0044] At the same time, two rolls of lithium film (lithium with plastic film support, lithium thickness 10um, width 145mm) and the integrated film material in the middle are unwound and rolled to obtain a lithium composite negative electrode with its own tabs.
[0045] Example 2
[0046] The current collector layer is selected to be a carbon nanotube film with a width of 150 mm and a length of 1000 meters. A 3 mm wide conductive adhesive layer is coated on an edge area of one side of the carbon nanotube film, and no conductive adhesive is coated on other areas of the carbon nanotube film.
[0047] A 150mm wide carbon nanotube film and a 20mm wide copper foil (6um thick) were unwound at the same time. After the 3mm wide conductive adhesive layer area of the carbon nanotube film and the 3mm wide area at the edge of the copper foil were completely matched, the carbon nanotube film and the copper foil were rolled by a rolling device to become an integrated film material.
[0048] At the same time, two rolls of lithium metal tape (lithium thickness 20um, width 147mm) and the integrated film material in the middle are unwound and rolled to obtain a lithium composite negative electrode with its own tabs.
[0049] Example 3: The negative electrode uses the lithium composite negative electrode prepared in Example 1, and the positive electrode uses NCM (811 nickel-cobalt-manganese ternary positive electrode), and the coating surface density is 50 mg / cm 2 The positive electrode sheet area is 43*56mm, the negative electrode sheet area is 45*58mm, and the PE material separator is used to assemble a 4-positive and 5-negative soft-pack battery. The electrolyte uses 1M LiPF6, EC (ethylene carbonate): EMC (ethyl methyl carbonate) = 3:7 (vol / vol). The negative electrode sheet, NCM ternary positive electrode sheet and separator are assembled into a soft-pack battery with the help of a stacking machine. The test voltage range is 2.8-4.35V, the charging current is 0.2C, and the discharge current is 0.5C.
[0050] Comparative Example 1:
[0051] The upper and lower rolls of lithium film are unwound at the same time, the thickness of the lithium film is 10um, and the current collector copper foil (thickness 8um) in the middle position is unwound at the same time, the width of the copper foil is 175mm, and the width of the lithium film is 145mm. The unwinding speed of the copper foil and the metallic lithium film is the same. The three-layer strip is pressure-compounded to obtain a lithium composite negative electrode with copper foil tabs.
[0052] Comparative Example 2: The negative electrode used was the lithium composite negative electrode of Comparative Example 1, and the assembly of the positive electrode, separator, electrolyte and soft-pack battery was the same as that of Example 3.
[0053] Table 1 Tensile strength values of the junction between the current collector and the tab
[0054] name Tensile strength of conductive adhesive joint material / MPa Example 1 80.3 Example 2 80.1
[0055] The tensile strength of the tested carbon nanotube film material is 78.9MPa, and the tensile strength of the 10um thick copper foil is 210.3MPa. It can be seen from the table data that the tensile strength of the material at the junction of the conductive adhesive is very strong, and the carbon nanotube film and the copper foil are not easy to break, and can form a current collecting whole well, which can be mass-produced and applied.
[0056] Table 2 Battery specific energy comparison
[0057] Group Specific energy of battery cell (wh / kg) Number of cycles (capacity decay 80%) Example 3 427.6 128 Comparative Example 2 400.3 103
[0058] It should be understood that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium composite negative electrode with a self-contained tab, characterized in that: The lithium composite negative electrode comprises: Two negative electrode layers: upper and lower; a current collector layer sandwiched between two negative electrode layers, wherein the width of the current collector layer is greater than that of the negative electrode layer, one end of the current collector layer is aligned with the negative electrode layer in the width direction, and the other end has a portion exposing the negative electrode layer; and Extreme ears, The portion of the current collector layer exposed from the negative electrode layer and the tab are bonded together via a tab bonding portion.
2. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The tab bonding portion is an adhesive layer located between the portion where the negative electrode layer is exposed and the tab.
3. The lithium composite negative electrode with a self-contained tab according to claim 2, characterized in that: The thickness of the current collector layer is 5-50 um.
4. The lithium composite negative electrode with a self-contained tab according to claim 2, characterized in that: The width of the adhesive layer is 2-10 mm.
5. The lithium composite negative electrode with a self-contained tab according to claim 2, characterized in that: The thickness of the tab is 4-50 um.
6. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The negative electrode layer is a metal lithium layer or a lithium alloy layer.
7. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The thickness of the negative electrode layer is 1-100 um, and the width is 50-1400 mm.
8. The lithium composite negative electrode with a self-contained tab according to claim 1, characterized in that: The thickness of the electrode tab does not exceed the thickness of the negative electrode layer.
9. The lithium composite negative electrode with a tab according to claim 1, characterized in that: The lithium composite negative electrode is a continuous web with a length of 1-2000 m.
10. A lithium battery, characterized in that: The lithium battery comprises the lithium composite negative electrode with a self-contained tab according to any one of claims 1 to 9.
Citation Information
Cited By
Copper-lithium composite belt welding method
CN120438783A